UPAYA MENINGKATKAN MINAT BELAJAR SISWA MENGGUNAKAN MODIFIKASI PERMAINAN TAVOL (TAKRAW DAN VOLI) UNTUK SISWA KELAS VIII SMP KANISIUS JUWANA - Beny Widya Priadana; Dewi Sari Jayanti; M. Iqbal Tawakkal (Sekolah Tinggi Pariwisata Mataram, 2020)
The background of this research is quantitative descriptive research that is about efforts to increase student learning interest using a modification of the game tavol. In this study the number of eighth grade students of kanisius juwana middle school were 16 students consisting of 8 men and 8 women with efforts to improve. Student interest in using tavol modifications. In this study before the pre-test was conducted to measure the initial interest of eighth grade students of kanisius juwana. Based on the calculation, the sig value 0.631>0.05 so it canbe concluded. Pretest data were normal. Significant figures obtained through the t test were p=0.00<0.05. thus it can be concluded that Ha was rejected. The average result of interest in lerning to fit under a volleyball before being given a modified learning design is tavol 10.88 the maximum value 10.88 the maximum value is 16 and the minimum value. The average result of learning interest after being given a modification design of tavol is 13.56, a maximum value of 19 and minimum value of 10, it can be concluded that efforst to increase student interest in using the modification of tavol are successful. The suggestion in this research is that it needs to create a pleasant atmosphere so that in an effort to increase students interest is learning they do not feel boed.